Discotheque in Semarang and It’s Social Consequences, 1970-1998 - Petra Wahyu Utama; Sutejo K. Widodo; Dhanang Respati Puguh (Diponegoro University, 2019)
This study focuses on analysis regarding the development of the discotheque as an impact of the disco trend which occurred at the beginning of the Orde Baru reign. Many places facilitated the disco-lovers which were begun with the development of Discobar, Night Club, then Discotheque. They were used as a medium of socialization and became a symbol of modernity which brought social consequences for the society in Semarang. This research discovers; firstly, the emergence of the discotheque and some nightclubs during the Orde Baru governance became an opportunity for the entrepreneurs who work in this field. For the governance, the amount of money circulation in this sector was considered an effective way to increase revenue either officially or through bribery. The existence of discotheques and any nightclubs were considered having an important role in reducing unemployment. In practice, the permission related to establishing the discotheques became much easier to be issued by the government of Semarang. Secondly, the existence of discothèques did not always affect positively the society. Negative behaviors, such as drinking alcohol, violence, drugs using, corrupted law officials, bribery crime, and also hidden prostitution are always stigmatized with the existence of discothèque. Thirdly, those negative emergences could not be separated by various orientations, such as economic and psychological orientation, as well as various motives, such as mental health, socio-economic, and situational which possessed by each individual. Fourthly, these social consequences made the government doing various efforts to overcome it. These efforts involved preventive ways, such as the education of alcohol and drugs abuse and data collection toward people with the genital disease, then preventive action, such as security patrol and counseling; as well as the repressive-coercive way, such as the raids, and the punishment for alcohol vendors and drugs dealer. In addition, they regulated the hidden prostitution in the discothèque area, disciplined the law enforcement officials and revoked the operational license as the last action to parse the issue which reached the alarming standard.